PENGARUH EDUKASI VIDEO PENCEGAHAN OBESITAS TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI (Jurnal Kesehatan Siliwangi, 2021)
This study is motivated by the increasing prevalence of diabetes mellitus which is impacted by lack of physical activity, excess weight and obesity. The incidence of obesity is the biggest challenge, even who declared it a global epidemic. Based on RISKEDAS 2018 obesity shows a figure of 21.8%. The highest incidence of obesity in adolescents was 59.2% of 13-15 year olds. The research aims to analyze the influence of education through video on young women's knowledge and attitudes about obesity prevention at one SMPN in Bandung regency 2021. The method used was quantitative design, with one-group pretest-posttest design. The study subjects numbered 38 overweight grade VIII students. Knowledge and attitude data were collected using questionnaires, and analyzed using the Wilcoxon Signed Test. The results showed that the improvement was seen from the category of good in the original knowledge only 31 to 37 people, while the original attitude was categorized enough as many as 27 people to 31 people in the good category. Based on the analysis test conducted there is a significant value to knowledge of 0.020 and attitude of 0.000 which means < 0.05, it can be concluded that there is a significant impact of education through video on improving the knowledge and attitude of young women in class VIII at one of the SMPN in Bandung Regency. This video media can be used as an alternative media to educate junior high school students about obesity prevention.